Caveman Dave - Sharratt, Nick. (Cambridge, Mass. : Candlewick Press, 1995)
Caveman Dave is very brave, but his sister, Ava, is even braver.
"First published in Great Britain in 1994 by Walker Books Ltd., London"--T.p. verso.
Keywords: Humorous stories; Stories in rhyme